218k views
0 votes
3(2x-1)=4x+12 what value of X satisfies the equation above

User Mschmidt
by
5.5k points

2 Answers

5 votes

Answer:


7(1)/(2)

Explanation:


3(2x-1)=4x+12\\

Use 3 to open the bracket


3(2x-1) = 6x -3\\\\ 6x-3 = 4x+12\\

Collect like terms and simplify


6x-4x = 12+3\\2x = 15

Divide both sides of the equation by 2


(2x)/(2) = (15)/(2) \\\\x = (15)/(2) = 7(1)/(2)

User Ashutosh Mishra
by
5.5k points
4 votes

Answer:


x = (15)/(2) \\\\x =7(1)/(2)

Explanation:


3\left(2x-1\right)=4x+12\\\\\mathrm{Expand\:}3\left(2x-1\right):\quad 6x-3\\6x-3=4x+12\\\\\mathrm{Add\:}3\mathrm{\:to\:both\:sides}\\6x-3+3=4x+12+3\\\\Simplify\\6x=4x+15\\\\\mathrm{Subtract\:}4x\mathrm{\:from\:both\:sides}\\6x-4x=4x+15-4x\\\\Simplify\\2x =15\\\\\mathrm{Divide\:both\:sides\:by\:}2\\(2x)/(2)=(15)/(2)\\\\Simplify\\x = 15/2

User Sez
by
5.6k points